Investigation of genes expression of the JAK/STAT signalling pathway and AMPs in the presence of Borrelia spirochetes in Ixodes ricinus - Magdalena Szczotko; Sandra Antunes; Ana Domingos; Małgorzata Dmitryjuk (Scientific Reports)
Abstract Multicellular animals need to control the spread of invading pathogens. This is a particular challenge for blood-feeding vectors such as ticks, which ingest large amounts of blood potentially laden with harmful microorganisms. Ticks have a basic innate immune system and protect themselves from infection through innate immune responses involving pathways such as Janus kinase (JAK) or the signalling transducer activator of transcription (STAT). Direct antimicrobial defence occurs through the rapid synthesis of numerous antimicrobial agents including antimicrobial peptides (AMPs). The tick Ixodes ricinus is one of the main vectors of the Lyme disease pathogen, the spirochete Borrelia burgdorferi sensu lato. Data suggest that the JAK/STAT signalling pathway controls the expression of AMPs and regulates the infection of the pathogen in the tick body. The innate immune system during the off-host period keeps the level of spirochete infection in check. Spirochetes may influence the innate immune response in ticks. Therefore, the aim of this study was to analyse the expression of the genes related to the JAK/STAT pathway and selected AMPs in questing ticks in which B. burgorferi s.l. was detected. In the ticks infected with spirochetes, overexpression of genes related to the JAK/STAT signalling pathway was observed in the case of STAM and SOCS genes. AMPs genes such as def1, ric, lzs were overexpressed with different expression patterns. The results obtained suggest that AMPs may be involved in infection management in ticks.